1996
DOI: 10.1155/1997/53453
|View full text |Cite
|
Sign up to set email alerts
|

Symptomatic Giant Cavernous Haemangioma of the Liver: Is Enucleation a Safe Method?

Abstract: Twenty-three patients with symptomatic giant hemangioma of the liver were treated by surgery between 1979 and 1996 at the department of General Surgery, Faculty of Medicine, University of Çukurova. Twenty-three enucleations were performed in 21 patients, left lateral segmentectomy in one patient and enucleation plus left lobectomy in one patient. The tumors were enucleated along the interface between the hemangioma and normal liver tissue. The diameters of the tumors ranged from 5×5 to 25×15 cm. The mean blood… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
1

Year Published

1998
1998
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 13 publications
0
7
0
1
Order By: Relevance
“…Similar to our experience, others have found it to result in less blood loss (400-922 ml) and require less operating time (204 min) compared to liver resection (blood loss 1000-2080 ml; operation time 258-262 min). 10,[12][13][14] Zimmermann and Baer 15 described the well-formed tumour-liver interface and its surgical application. Since there are no bile ducts traversing the plane between the liver and the haemangioma, enucleation does not result in postoperative bile leak, which is an infrequent, but troublesome, complication of liver resection.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to our experience, others have found it to result in less blood loss (400-922 ml) and require less operating time (204 min) compared to liver resection (blood loss 1000-2080 ml; operation time 258-262 min). 10,[12][13][14] Zimmermann and Baer 15 described the well-formed tumour-liver interface and its surgical application. Since there are no bile ducts traversing the plane between the liver and the haemangioma, enucleation does not result in postoperative bile leak, which is an infrequent, but troublesome, complication of liver resection.…”
Section: Discussionmentioning
confidence: 99%
“…In 1988, Alper et al [9] first described enucleation, which is based on the macroscopic observation that hemangiomas are encapsulated by a dissection plane between the liver parenchyma and the hemangioma [10]. Most authors advocated enucleation because it is safer and quicker, with fewer overall complications and less blood loss [6,11,12,13], while others concluded that results were similar between enucleation and anatomic resection [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Simple enucleating has been reported to be safe without major blood loss. 4,9 Surgical resection is the treatment of choice for a giant symptomatic hemangioma, and if it is unresectable, then liver transplantation may be considered. 10 Our experience indicates that resection of giant hemangioma of the liver is safe.…”
Section: Discussionmentioning
confidence: 99%